2021
DOI: 10.1038/s41598-021-82686-3
|View full text |Cite
|
Sign up to set email alerts
|

Targeting galectin-3 with a high-affinity antibody for inhibition of high-grade serous ovarian cancer and other MUC16/CA-125-expressing malignancies

Abstract: The lectin, galectin-3 (Gal3), has been implicated in a variety of inflammatory and oncogenic processes, including tumor growth, invasion, and metastasis. The interactions of Gal3 and MUC16 represent a potential targetable pathway for the treatment of MUC16-expressing malignancies. We found that the silencing of Gal3 in MUC16-expressing breast and ovarian cancer cells in vitro inhibited tumor cell invasion and led to attenuated tumor growth in murine models. We therefore developed an inhibitory murine monoclon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…The therapeutic mechanism of muAR9.6 distinguishes it from other MUC16-targeted antibodies, including those reported from our laboratories (10,13,15,16,24,25,31,32). Motivated by its novelty, we set out to validate the in vitro cell binding of muAR9.6 and explore the in vivo behavior of a 89 Zr-labeled variant of the antibody in preclinical tumor models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapeutic mechanism of muAR9.6 distinguishes it from other MUC16-targeted antibodies, including those reported from our laboratories (10,13,15,16,24,25,31,32). Motivated by its novelty, we set out to validate the in vitro cell binding of muAR9.6 and explore the in vivo behavior of a 89 Zr-labeled variant of the antibody in preclinical tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…However, Reinartz et al have shown that SKOV3 cells have very low levels of MUC16 transcript (mRNA), and though they reported no binding of anti-CA125 antibodies to SKOV3 cells, Felder et al reported marginal binding of OC125-like MUC16-binding antibodies to SKOV3 cells via flow cytometry. Plausibly, alternative splicing or post-translational modifications may be causing the AR9.6 epitope to be expressed on SKOV3 cells, leading to marginal binding to this cell line that is otherwise considered MUC16-negative (14,32). In our hands, using muAR9.6 as the primary antibody for Western blotting of SKOV3 cell lysate revealed binding of the antibody to a low molecular weight band observed in the other MUC16-positive cell lines such as OVCAR3, Capan-2, S2-2028 and T3M-4 (Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…Studies to inhibit Galectin-3 classically focused on blocking the binding of carbohydrate substrates to the recognition domain. Reagents that are based on such a mechanism of action include carbohydrate mimetics (14), peptides that bind to the CRD (42), and, recently, function blocking antibodies (60). However, because the NTD-CTD interaction appears to be essential for the extracellular activity of Galectin-3, the inhibition of this interaction may afford an alternative approach.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies to inhibit Galectin-3 classically focused on blocking the binding of carbohydrate substrates to the recognition domain ( 14), ( 42), (58), galactomannins (59) and PTX008, a calixarene (50) may also target the NTD-CRD interaction. PTX008 contacts V202, K210, V211 and A216 located in the F-face of the CRD, which are also contacted by peptide-3 in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibodies are commonly used to block protein functions. Stasenko et al showed that invasion and proliferation were suppressed in high-grade serous ovarian cancer, and showed improved overall survival, in response to treatment with an anti-Gal-3 antibody [ 158 ]. Evidence shows that neutralizing antibodies may partially suppress the inhibition of lactose treatment [ 159 ].…”
Section: Available Inhibitors For Targeting Galectinsmentioning
confidence: 99%